A Systematic Review of Fear of Cancer Recurrence Among Indigenous and Minority Peoples - Anderson, Kate; Smith, Allan ‘Ben'; Diaz, Abbey; Shaw, Joanne; Butow, Phyllis; Sharpe, Louise; Girgis, Afaf; Lebel, Sophie; Dhillon, Haryana; Burhansstipanov, Linda; Tighe, Boden; Garvey, Gail (Frontiers in Psychology, 2021)
While cancer survivors commonly experience fear and anxiety, a substantial minority experience an enduring and debilitating fear that their cancer will return; a condition commonly referred to as fear of cancer recurrence (FCR). Despite recent advances in this area, little is known about FCR among people from Indigenous or other ethnic and racial minority populations. Given the high prevalence and poor outcomes of cancer among people from these populations, a robust understanding of FCR for these groups is critical. This review identified and aggregated existing literature on FCR amongst adult cancer survivors from Indigenous and minority populations. The review protocol was registered with PROSPERO in July 2020 (Registration number: CRD42020161655). A systematic search of bibliographic databases was conducted for relevant articles published from 1997 to November 2019. Data from eligible articles were extracted and quality appraised by two independent reviewers. Nineteen articles from four countries (United States of America, Canada, Australia and the United Kingdom) met the inclusion criteria, including 14 quantitative, 4 qualitative and 1 mixed-methods study. Only one article reported on an Indigenous population. Few studies reported on FCR prevalence (n=3) or severity (n=9). While the variation in tools used to measure FCR hindered a robust estimate of severity, results suggested some differences in FCR severity between minority and dominant populations, although these may have been due to study metholodological differences. Few factors were reported as being associated with FCR in minorities across multiple studies. The qualitative synthesis found five themes associated with the lived experience of FCR: (i) variations in the lived experience of FCR; (ii) spirituality and worldview impacting on FCR; (iii) the importance of staying positive; (iv) complexities around support; and (v) increasing cancer knowledge. The findings of this review highlight differences in FCR across cultures and contexts, which reinforces the need for culturally-specific approaches to this condition. The dearth of research in this area is of concern given the significant burden of cancer in these populations. A deeper understanding of this condition among Indigenous and minority populations is critical to developing and delivering appropriate and effective psychosocial care for cancer survivors from these groups.